O viver na Cidade do Bem: tensões, conflitos e acomodações na vila operária de Luiz Tarquínio na BoaViagem/BA - Marilecia Oliveira Santos (2010)
The purpose of this Thesis is to study the Factory Workers Villa of Boa Viagem, in Salvador City, as a living space of workers. It explores the senses and meanings that the villa had for its residents, as well as many people involved in that experience. Through the analyses of the rules of conduct established by the company, this thesis intends to know the intentions of the company's control and how workers/residents understood this rules, sometimes chose to subject themselves to these determinations and other time performed efforts to make such spaces as their own places , trying to create territories of sociability and identities builder. The researched documentation revealed a mismatch between the memory constructed about the villa, as an idealized space, and the historic experience permeated with clashes, conflicts and tensions. The temporal clipping is from 1892, when the villa was inaugurated, to 1946/47, period when the new Internal Regulation of Working and Housing was created, submitted and approved by the Regional Labour Office.